Mining triggers extensive additional deforestation in sub-Saharan Africa - Oscar Morton; Christopher G. Bousfield; Prince Dégny Valé; Ieuan Lamb; Victor Maus; Robert G. Bryant; David P. Edwards (Nature, 2026)
Abstract Demand for minerals sourced from sub-Saharan Africa is expanding rapidly 1–5 . If poorly managed, mining expansion poses a key threat to tropical forests across the continent 6,7 . Here we present a spatiotemporal assessment of mining-driven deforestation of dense forests across Africa, using continent-wide data on post-deforestation land uses and a robust difference-in-differences framework to assess 16,627 mines between 2001 and 2020. In total, we find 187,000 hectares of direct mining-driven deforestation, that is, deforestation due to features directly associated with mining operations, such as pits, tailing ponds and spoil heaps. We estimate that mining also triggers an additional 8.0 percentage points (pp; 95% confidence interval (CI): 7.2–8.9 pp) increase in deforestation within 1 km of a mine compared with unmined areas. Increased levels of deforestation (1.1 pp, 95% CI: 0.7–1.5) persist up to 20 km from mines even after ten years. For every hectare of direct deforestation due to the mine footprint, mining triggers, on average, 34 hectares of additional offsite loss within five years through ancillary activities, including agriculture and settlements. Mines extracting cobalt and copper—key energy transition minerals—caused the highest amount of additional deforestation. Embedding offsite deforestation levels into environmental impact assessments for new mining projects will be key to ensuring zero-deforestation or no-net-loss supply chains for critical minerals and reduce future mining-driven forest losses in sub-Saharan Africa.